2014
DOI: 10.1002/adma.201403560
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Organic Optoelectronic Sensors for Medicine

Abstract: Organic optoelectronic devices that can be used to make compact, wearable sensors for medicine and sports are shown and two examples are given: a tissue‐oxygenation sensor and a muscle‐contraction sensor. It is demonstrated how the muscle‐contraction sensor on a volunteer's arm can successfully control the robot arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
154
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 38 publications
0
154
0
Order By: Relevance
“…Unlike the inorganic optoelectronics used in commercially available pulse oximeters, the fl exible form factors of organic LEDs (OLEDs) and organic photodetectors (OPDs) allow for an oximeter that has a conformal fi t to the human body. [ 6,85 ] Lochner et al have demonstrated a transmission-mode pulse oximetry probe composed of solution-processed OLEDs and a printed OPD. [ 6 ] The active layer of the OPD is a bulk heterojunction donor/acceptor blend of [6,6] .…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the inorganic optoelectronics used in commercially available pulse oximeters, the fl exible form factors of organic LEDs (OLEDs) and organic photodetectors (OPDs) allow for an oximeter that has a conformal fi t to the human body. [ 6,85 ] Lochner et al have demonstrated a transmission-mode pulse oximetry probe composed of solution-processed OLEDs and a printed OPD. [ 6 ] The active layer of the OPD is a bulk heterojunction donor/acceptor blend of [6,6] .…”
Section: Reviewmentioning
confidence: 99%
“…[ 85 ] The OLED is placed in between the two OPDs, each with a different fi lter to allow the OPD to read light with a peak wavelength of 610 or 700 nm. The OLED and OPD were placed onto a subject's forearm with 20 mm spacing in order to probe the oxygen saturation of muscle tissue, and successfully showed the change in the concentration of oxy-hemoglobin in the tissue upon induction and termination of ischemia induced in the arm.…”
Section: Reviewmentioning
confidence: 99%
“…Interest in stretchable electronics has grown significantly in recent years, driving a need for soft and stretchable materials that can sustain high strains and still fulfill their function in applications such as human wearable sensors for biomechanics studies and health monitoring [1][2][3][4] , or feedback sensors in soft robotics. [5][6][7][8] Although many stretchable conductors exist, including liquid metals, [9,10] nanowires, [11,12] nanoribbons [13] , pre-stretched elastomer fibers with conductive coatings, [14] and micro-cracked metals, [15,16] these materials have generally been unable to achieve high levels of optical transparency while maintaining high conductivities and stretchability; a feature that would enable their use in optogenetics [17] or allow optical imaging of the underlying substrate.…”
mentioning
confidence: 99%
“…OLED is also an upcoming technology for solid state lighting5, since it can provide uniform illumination over a large area6 and offers the possibility for complex lighting designs and patterns. OLEDs have also been successfully implemented in wearable sensing devices for applications in medicine and robotics78.…”
mentioning
confidence: 99%